Bifurcation of quiescent H-mode to a wide pedestal regime in DIII-D and advances in the understanding of edge harmonic oscillations. (14th June 2017) - Chen, Xi; Burrell, K.H.; Osborne, T.H.; Barada, K.; Ferraro, N.M.; Garofalo, A.M.; Groebner, R.J.; McKee, G.R.; Petty, C.C.; Porkolab, M.; Rhodes, T.L.; Rost, J.C.; et al.
Abstract: New experimental studies and modelling of the coherent edge harmonic oscillation (EHO), which regulates the conventional Quiescent H-mode (QH-mode) edge, validate the proposed hypothesis of edge rotational shear in destabilizing the low- n kink-peeling mode as the additional drive mechanism for the EHO. The observed minimum edge E   ×   B shear required for the EHO decreases linearly with pedestal collisionality ν e ∗, which is favorable for operating QH-mode in machines with low collisionality and low rotation such as ITER. In addition, the QH-mode regime in DIII-D has recently been found to bifurcate into a new 'wide-pedestal' state at low torque in double-null shaped plasmas, characterized by increased pedestal height, width and thermal energy confinement (Burrell 2016 Phys. Plasmas 23 056103, Chen 2017 Nucl. Fusion 57 022007). This potentially provides an alternate path for achieving high performance ELM-stable operation at low torque, in addition to the low-torque QH-mode sustained with applied 3D fields. Multi-branch low- k and intermediate- k turbulences are observed in the 'wide-pedestal'. New experiments support the hypothesis that the decreased edge E   ×   B shear enables destabilization of broadband turbulence, which relaxes edge pressure gradients, improves peeling-ballooning stability and allows a wider and thus higher pedestal. The ability to accurately predict the critical E   ×   B shear for EHO and maintain high performance QH-mode at low torque is an essential requirement for projecting QH-mode operation to ITER and future machines.